ARTIFICIAL TASK AS SCIENTIFIC DEFENSE: PHILOSOPHICAL AND HISTORICAL ASPECT - Merezhko, Julia; Rumyantsevа Svetlana (Educological discourse, 2018)
The article deals with concept of artistic taste and its aspects. The author analyzes the process of establishing and development of taste as a philosophic and historical definition. On the one hand, the current theme is very important for preserving the spirituality of Ukrainian nation. On the other hand, artistic tastes characterized the new generation of music teachers whom can popularize artistic communication with classical and contemporary music among children and youth. The paper describes how were identified the definition the taste by famous philosophists (e.g., B. Gracián, Ch. Batteux, Voltaire, D. Hume, J. J. Winckelmann , J. H. Sulzer, I. Kant) and psychologists and pedagogues (for example, O. Molchanova, R. Naumov, O. Larmin, V. Shatska and others). The author summarized the theoretical aspects of essence of artistic taste and its components. The artistic taste considered as a key concept of the personality’s aesthetic conscious. It follows the connection among artistic interests, aesthetic ideals та artistic judgments. The artistic taste plays an important role in the process of personality’s formation, especially of the young generation. As a result, the author proposed to explore new methods of formation of artistic tastes in different aged groups of children and youth. In addition, it will be useful for following the new researches of the aesthetic potential of classical music in the process of artistic tastes’ formation.